2010
DOI: 10.1111/j.1464-410x.2010.09735.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced ultrasonography of the prostate: various imaging findings that indicate prostate cancer

Abstract: Study Type – Diagnostic (non‐consecutive case series) 
Level of Evidence 3b What’s known on the subject? and What does the study add? Contrast‐enhanced ultrasonography (CEUS) can visualize some prostate cancer lesions. Findings suggestive of cancer have been defined as rapid contrast enhancement; increased contrast enhancement. CEUS could be useful for targeted biopsy in patients with a PSA level <10 ng/mL. The CEUS findings suggestive of prostate cancer are more varied than previously reported. Low‐echogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 25 publications
2
20
0
1
Order By: Relevance
“…24 Sano et al expanded the definition of CEUS malignancy according to the theory that various histopathological cancer types can coexist in a single patient. 25 Evaluation of 13 patients before RP revealed variable behavior of contrast enhancement. Consistent with the findings of Sano et al, we observed suspicious perfusion (hypoperfusion or hyperperfusion) of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Sano et al expanded the definition of CEUS malignancy according to the theory that various histopathological cancer types can coexist in a single patient. 25 Evaluation of 13 patients before RP revealed variable behavior of contrast enhancement. Consistent with the findings of Sano et al, we observed suspicious perfusion (hypoperfusion or hyperperfusion) of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat intravenous injections of contrast agent or specific techniques that enable reperfusion, such as the replenishment technique, might improve the evaluation of multiple cross sections. 25 The evaluation of CEUS behavior might be affected by patient position, which could have an influence on prostatic blood flow. 29 Therefore, the supine position may affect the outcome of CEUS in future examinations.…”
Section: Discussionmentioning
confidence: 99%
“…For urologists, intravascular CEUS may potentially play a role in characterizing renal cystic lesions, 21 staging vascularized bladder masses, 22,23 and detecting prostate cancer. 24 Besides intravascular injection, other routes of ultrasound contrast administration have been reported for urologic application. These include intravesical CEUS, which has become an option for the diagnosis of vesicoureteral reflux in pediatric patients, 25 and voiding urosonography, which shows potential for evaluating the urethra.…”
Section: Figmentioning
confidence: 99%
“…In addition to the proven value in echocardiography there is a growing body of literature elucidating the value of contrast-enhanced sonography (CEUS) in distinguishing benign from malignant liver tumors and in the evaluation of non-hepatic malignancies in adults [6][7][8][9]. More recently, reports indicate their value for quantifying solid tumor response to anti-angiogenic agents [10].…”
Section: Introductionmentioning
confidence: 99%